SYARIAT DALAM PERSPEKTIF TAREKAT (Studi Konfirmatif Atas Hasil Penelitian Muh. Gitosaroso Tahun 2016 Pada Jamaah Tarekat Haq Naqsyabandi di Kota Pontianak) - Elmansyah Elmansyah (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2019)
This study is a confirmative study of Muh. Gitosaroso in 2016, who discovered that the congregation of the Haq Naqsyabandi Congregation in Pontianak tended to prioritize the essence of shari’ah. This study was conducted from mid-September 2018 until the end of December 2018. The purpose of this study was to determine the extent of changes that occurred in the congregation of the Haq Naqsyabandi congregation in Pontianak, related to their views on shari’ah. The method used is descriptive method - analysis of the results of interviews in the field with the attitudes and actions of the congregation everyday. The results showed that there had been a significant change in the congregation of the Haq Naqsyabandi, related to their views on shari’ah. The congregation is active in the mosque for congregational prayers, active in the economy, and active in various social activities